2012
DOI: 10.1016/j.jmb.2012.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Directed Evolution of the Forkhead-Associated Domain to Generate Anti-Phosphospecific Reagents by Phage Display

Abstract: While affinity reagents are valuable tools for monitoring protein phosphorylation and studying signaling events in cells, generating them through immunization of animals with phosphopeptides is expensive, laborious and time consuming. An attractive alternative is to use protein evolution techniques and isolate new anti-phosphopeptide binding specificities from a library of variants of a phosphopeptide-binding domain. To explore this strategy, we attempted to display on the surface of bacteriophage M13, the N-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 43 publications
(54 reference statements)
1
22
0
Order By: Relevance
“…Our findings confirm that the pT+3 position is critical for binding for this FHA domain variant. This is consistent with the previous finding of Pershad et al (22), which demonstrated the importance of the pT+3 in the peptide ligand for the FHA domain that binds MAPK3. However, it is likely that other positions in the peptide likely contribute somewhat to binding, as the peptide AAApTAALA does not bind to the same level as the target sequence, LLPpTPPLS.…”
Section: Resultssupporting
confidence: 94%
See 4 more Smart Citations
“…Our findings confirm that the pT+3 position is critical for binding for this FHA domain variant. This is consistent with the previous finding of Pershad et al (22), which demonstrated the importance of the pT+3 in the peptide ligand for the FHA domain that binds MAPK3. However, it is likely that other positions in the peptide likely contribute somewhat to binding, as the peptide AAApTAALA does not bind to the same level as the target sequence, LLPpTPPLS.…”
Section: Resultssupporting
confidence: 94%
“…To generate recombinant affinity reagents that are phosphothreonine-specific, a phage display library was constructed by randomizing residues in the β4-β5 and β10-β11 loop regions of a thermostable variant (FHA1G2) of the FHA1 domain of the yeast Rad53 protein (22, 28) (Fig. 1A).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations